A STUDY ON THE EFFECTIVENESS OF CROSSWORD PUZZLE AS COMPARED TO CONVENTIONAL METHOD IN TEACHING VOCABULARY - Nelson B Pandjaitan; Erwin Simbolon; Anne Lou (Journal of Language Pedagogy, 2011)
This study is entitled “The Effectiveness of Crossword Puzzle as Compared TheConventional Method in Teaching Vocabulary.”The research was administered to answer the question “Is crossword puzzle ascompared to other methods effective in improving student vocabulary achievement?” The datawere collected through pretest and posttest, administered to 35 student and the data wasanalyzed by using T-test.The participants of this study were the grade five elementary pupils of kartika elementaryschool. in section 5A there were 34 pupils who were taught using conventional method andsection 5B there were 35 pupils who were taught using crossword puzzle method. The age ofthe participants were between 11-15 years old.From the computation of the pretest and posttest, the result mean of pretest controlgroup=51.17, the result mean of pretest experimental group=55.14. and the mean posttestcontrol group= 56.61,the mean posttest experiment group= 63.42. The result shows that t counted=2.106>t table = 1,684. There is significant different crossword puzzle method effective toimprove vocabulary skills.The researcher hopes that the finding of present crossword puzzle method could give somecontribution to the improvement vocabulary especially for the students of Kartika X-3,Parompong, Bandung.